Revisiting the role of novel weight management medications and bariatric surgery - LIANG Hui (Xin yixue)
The global prevalence of obesity has continued to rise globally over the past two decades. Obesity is closely associated with increased risk of metabolic， cardiovascular， and other diseases， reduced quality of life and shortened life expectancy. Bariatric surgery is recognized as a highly effective weight loss measure， with studies showing its effects lasting more than 10 years. Moreover， bariatric surgery not only leads to weight loss but also improves cardiovascular and metabolic risk factors， such as type 2 diabetes， hypertension， and dyslipidaemia. It also demonstrates sound therapeutic effects on other obesity-related diseases， such as polycystic ovary syndrome（PCOS）， sleep apnea， and osteoarthritis. Studies have shown that patients undergoing bariatric surgery have reduced all-cause mortality， cardiovascular events and cancer risk.The emergence of glucagon-like peptide-1 receptor agonist therapies （GLP-1 RA， semaglutide） and GLP-1/GIP dual receptor agonist （tirzepatide） has demonstrated significant weight loss effects with continuous use. Similar to bariatric surgery， these drugs can improve outcomes for type 2 diabetes， cardiovascular mortality， and other obesity-related complications. The article compares bariatric surgery with enteral proinsulin agonists in terms of weight loss efficacy， complication rates， risk profile， cost-effectiveness， and accessibility， explores the value and promise of these popular drugs and bariatric surgery in the treatment of obesity.